2004
DOI: 10.1002/ijc.20340
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of malignant growth of human breast cancer cells by ectopic expression of integrinlinked kinase

Abstract: Allelic loss at the short arm of chromosome 11 is one of the most common and potent events in the progression and metastasis of breast cancer. Here, we present evidence that the Integrin-Linked Kinase (ILK) gene maps to the commonly deleted chromosome 11p15. Genetic alterations that occur in breast cancer are believed to be of importance for initiation as well as progression of the disease. These genetic alterations lead to the loss or activation of a number of critical genes, such as those involved in cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 42 publications
(49 reference statements)
3
24
2
1
Order By: Relevance
“…Previous studies have suggested that a region of LOH lies over the ILK locus in numerous cell types, including ERMS, breast carcinoma, and non-small cell lung carcinoma (4). Similarly, ILK functions as a tumor suppressor in MDA-MB-435 breast carcinoma cells, which display LOH at this locus (17). We have extended these results to suggest that ILK functions as a growth suppressor in one putative progenitor cell population for RMS tumors.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous studies have suggested that a region of LOH lies over the ILK locus in numerous cell types, including ERMS, breast carcinoma, and non-small cell lung carcinoma (4). Similarly, ILK functions as a tumor suppressor in MDA-MB-435 breast carcinoma cells, which display LOH at this locus (17). We have extended these results to suggest that ILK functions as a growth suppressor in one putative progenitor cell population for RMS tumors.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, ILK expression correlates in many tumor and normal tissues with areas of increased differentiation (13) and can cooperate with ionizing radiation to induce apoptosis in some cancer cells (14)(15)(16). Finally, overexpression of wild-type, but not mutant, ILK could limit tumor formation in MDA-MB-435 xenografts (17), although the mechanism for this finding was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…ILK is reported to regulate integrin-mediated cell adhesion and invasion, E-cadherin expression and ECM assembly (Delcommenne et al, 1998;Chen et al, 2004;Edwards et al, 2005;Filipenko et al, 2005). ILK activation is regulated in a phosphatidylinositol 3-kinase (PI3-K)-dependent manner by adhesion to ECM and by growth factors and cytokines (Hannigan et al, 2005;Larue and Bellacosa, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In addition, elevated ILK expression is found in more differentiated regions of solid tumors, 12 and ILK overexpression induces differentiation of L6 rat myoblasts 13 and suppresses MDA-MB-435 breast carcinoma xenograft growth. 14 Further, ILK overexpression synergizes with ionizing radiation to induce apoptosis in A549 non-small cell lung carcinoma (NSCLC), HL60 acute promyelocytic leukemia and Jurkat T cells. 15,16 While these studies indicate a potential growth-suppressive role for ILK in different cellular contexts, limited mechanistic insight has been uncovered.…”
Section: Introductionmentioning
confidence: 99%